Bacterial, viral, and fungal infection‐related risk of Parkinson's disease: Meta‐analysis of cohort and case–control studies - Wang, Hui (Brain Behav, 2020)
AIMS: Recent studies showed that patients with various bacterial, viral, and fungal infections might be at increased risk of Parkinson's disease (PD). However, the risk of PD in patients with each specific infection varied. This meta‐analysis estimated the association between various infections and PD risk. METHODS: Literature published from January 1965 to October 2019 in PubMed and EMBASE databases was searched. Data were extracted and pooled using random/fixed effects model. Sensitivity analysis and meta‐regression were also performed to analyze the source of heterogeneity. Publication bias was estimated by the trim and fill. RESULTS: Twenty‐three out of 6,609 studies were included. Helicobacter pylori (HP; pooled OR = 1.653, 1.426–1.915, p < .001), hepatitis C virus (HCV; pooled OR = 1.195, 1.012–1.410, p = .035), Malassezia (pooled OR = 1.694, 1.367–2.100, p < .001), and pneumoniae (pooled OR = 1.595, 1.020–2.493, p = .041) infection were associated with increased PD risk. Influenza virus, herpes virus, hepatitis B virus, scarlet fever, mumps virus, chicken pox, pertussis, German measles, and measles were not associated with PD risk. After antiviral treatment against HCV reduced the risk of PD in patients with HCV infection (OR = 0.672, 0.571–0.791, p < .001). Significant heterogeneity exists among the included studies. CONCLUSION: Patients with infection of HP, HCV, Malassezia, pneumoniae might be an increased risk of PD. Antiviral treatment of HCV could reduce the risk of PD.